Immune-Mediated Organ-Specific Reactions to COVID-19 Vaccines: A Retrospective Descriptive Study - Carmen Ruiz-Fernández; Ricardo Cuesta; Susana Martín-López; Javier Guijarro; Arturo López Gómez de las Huertas; Mikel Urroz; Laura Miguel-Berenguel; Miguel González-Muñoz; Elena Ramírez (MDPI AG, 2023)
Severe acute respiratory syndrome coronavirus 2 caused the global COVID-19 pandemic and public health crisis, and it led to the rapid development of COVID-19 vaccines, which can cause rare and typically mild hypersensitivity reactions (HRs). Delayed HRs to COVID-19 vaccines have been reported, and the excipients polyethylene glycol (PEG)2000 and polysorbate 80 (P80) are the suspected culprits. Skin patch tests do not help in diagnosing delayed reactions. We aimed to perform lymphocyte transformation tests (LTT) with PEG2000 and P80 in 23 patients with suspected delayed HRs. Neurological reactions (n = 10) and myopericarditis reactions (n = 6) were the most frequent complications. Seventy-eight percent (18/23) of the study patients were admitted to a hospital ward, and the median time to discharge was 5.5 (IQR, 3-8) days. Some 73.9% of the patients returned to baseline condition after 25 (IQR, 3-80) days. LTT was positive in 8/23 patients (5/10 neurological reactions, 2/4 hepatitis reactions and 1/2 rheumatologic reactions). All myopericarditis cases had a negative LTT. These preliminary results indicate that LTT with PEGs and polysorbates is a useful tool for identifying excipients as causal agents in HRs to COVID-19 vaccines and can play an important role in risk stratification in patients with HRs.